2009
DOI: 10.1890/08-1891.1
|View full text |Cite
|
Sign up to set email alerts
|

A fish of many scales: extrapolating sublethal pesticide exposures to the productivity of wild salmon populations

Abstract: Abstract. For more than a decade, numerous pesticides have been detected in river systems of the western United States that support anadromous species of Pacific salmon and steelhead. Over the same interval, several declining wild salmon populations have been listed as either threatened or endangered under the U.S. Endangered Species Act (ESA). Because pesticides occur in surface waters that provide critical habitat for ESA-listed stocks, they are an ongoing concern for salmon conservation and recovery through… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
101
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 113 publications
(104 citation statements)
references
References 49 publications
(60 reference statements)
3
101
0
Order By: Relevance
“…An individual-based model was developed based on empirical data that explicitly links sublethal reductions in acetylcholinesterase activity to reductions in feeding behavior, food consumption, growth, and size at outmigration of sub-yearling chinook salmon (Oncorhynchus tshawytscha; [56]). Individual size was used to estimate sizedependent sub-yearling survival during the migration and transition to the sea.…”
Section: Case 3: Acetylcholinesterasementioning
confidence: 99%
“…An individual-based model was developed based on empirical data that explicitly links sublethal reductions in acetylcholinesterase activity to reductions in feeding behavior, food consumption, growth, and size at outmigration of sub-yearling chinook salmon (Oncorhynchus tshawytscha; [56]). Individual size was used to estimate sizedependent sub-yearling survival during the migration and transition to the sea.…”
Section: Case 3: Acetylcholinesterasementioning
confidence: 99%
“…For ethical reasons there may be restrictions on the quantity and type of laboratory testing permitted on such species, and in such cases application of population modeling can make the most out of limited test data. For example, Baldwin et al (2009) investigated the population-level effects of acetylcholinesterase (AChE) inhibiting pesticides on endangered Chinook salmon. Limited laboratory studies demonstrated that sublethal reductions of AChE activity resulted in decreased swimming and feeding behaviors.…”
Section: Population Modeling Adds Needed Value To Eramentioning
confidence: 99%
“…For example, a number of studies investigating the effects of spatial complexity in exposure scenarios indicate that inter-individual variability in exposure can either increase (Palmqvist and Forbes 2008) or reduce (Dalkvist et al 2009) risk compared to the standard homogeneous exposure scenarios typically assumed in risk assessment. Likewise, by incorporating realistic information on the species' ecology into a population model, Baldwin et al (2009) were able to show that the change in size when fish migrated to the ocean caused a reduction in individual survival over successive years and thereby reduced the population growth rate.…”
Section: Population Modeling Adds Needed Value To Eramentioning
confidence: 99%
“…Larval and juvenile stages of resident organisms are at particular risk in that they may be exposed during their most vulnerable developmental stages while using these habitats as nursery grounds (Beck et al 2003;Courrat et al 2009). Ultimately, the impacts of pesticides in aquatic environments can cascade from individuals to populations (Baldwin et al 2009), and subsequently decrease biodiversity (Beketov et al 2013) and alter community structure (Fleeger et al 2003;Rohr et al 2006;Macneale et al 2010), although the mechanisms behind these impacts can be varied and complex.…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, the population ecology of organisms often depends on behavioral outcomes (Weis et al 1999;Murphy et al 2008;Relyea and Edwards 2010). Behavior can thus be a powerful tool to link the sub-organismal effects of sublethal pesticide exposure to species interactions and populationlevel processes (Weis et al 2001;Baldwin et al 2009;Weis and Candelmo 2012).…”
Section: Introductionmentioning
confidence: 99%